Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages any spoilation of Germany, but would have agreed, with the representatives of German workers and technicians, about the contribution of exports which a Socialist Germany could make to rebuild Europe. The Russians continually bring up against the British in Germany that they preserve the big estates* whose owners were the leading militarists, and that they will not disband German Army formations, whose usefulness as Labour Corps does not excuse, in the Russian view, the evil of keeping Nazi officers in command. The British retort is to complain of the Iron Curtain that prevents food from the Eastern Zone reaching Western Germany. This may be true, but it is not helpful. On August 20th, in the House of Commons, Bevin made the grave statement that the basis of the Labour Cabinet's foreign policy was in keeping with that worked out by the Coalition Government. It is true that he added that this policy rested on the main agreement and co-operation between the Great Powers that emerged from the War. It had always been a cardinal point with many socialists, inside as well as outside the Labour Party, that the Churchill Government, in seeking to restore the Kings, capitalists, and colonies of 1939, was following a line which they hated and would alter if they could. Labour's Foreign Minister declared that in Greece his Party were supporting the policy of restoring law and order. This dreadful cliché has been the easy excuse of every tyrant down to Hitler and Franco. When the War ended, Trade Unionists and Socialists were in the majority in Greek Resistance and hoped to reconstruct their country. By the middle of 1946, the economic life of the country was still in ruins, prices enormously high, the Royalists — the party of the wealthy — voted in at an Election after British bayonets had crushed the Left, and the ex-King about to return to the country to which, in 1936, he had given Metaxas as a dictator. The Greek people have paid this high price for Churchill's wish, and Bevin's, that Greece should be secure as part of Britain's Mediterranean strategical position. Mr. Bevin said he was afraid that in Bulgaria, Rumania and Hungary one kind of totalitarianism was being replaced by another. Hardly a tactful phrase for Moscow ears, especially as the British Minister omitted to praise the overthrow of the great Hungarian landlords, the Magnates, bulwarks of feudalism in Eastern * Footnote: At the very end of Labour's first year, in June, 1946, the British Deputy-Commander, General Robertson, was timidly talking of breaking up big estates. 5 15X/2/98/21